POLITICAL CULTURE OF THE KASEPUHAN GELARALAM COMMUNITY IN SUKABUMI REGENCY, WEST JAVA - Dinar Meidiana; Endang Sulastri; Lusi Andriyani; Asep Setiawan (Universitas Muhammadiyah Jakarta, 2026)
The political culture of a society constitutes a pivotal component in the development of democracy. Within the context of democratic practice, the political orientations and cultures of modern urban societies differ significantly from those of traditional communities. As a pluralistic nation, Indonesia faces unique challenges in implementing democratic practices, particularly in general elections. In the Kasepuhan Gelaralam community, individuals are granted the agency to determine their chosen leaders within the electoral framework, as evidenced by the adoption of procedures aligned with national electoral laws (Election Law). Researching the political culture of the Kasepuhan community is both vital and compelling for advancing academic discourse and promoting democratic practices within traditional societies. Consequently, this study examines the democratic values and practices that shape the political culture of the Kasepuhan Gelaralam in Sukabumi Regency, West Java. Employing a qualitative descriptive method, data was collected through observation and interviews. The findings reveal that democratic practices and values are deeply embedded within the Kasepuhan Gelaralam community. In daily life, principles of freedom, equality, justice, humanity, and non- discrimination are manifested, with all individuals considered equal under the law (Sara, Nagara, and Mokaha). These values foster a just and civilized democracy within the Kasepuhan. Furthermore, the community exhibits varying cognitive, affective, and evaluative orientations across different electoral cycles (the 2020 Regional Election, the 2023 Village Head Election, and the 2024 General Election). Based on these political orientations, it is concluded that the political culture of the Kasepuhan Gelaralam can be classified as partially parochial and partially participant